High Prevalence of SARS-CoV-2 Genetic Variation and D614G Mutation in Pediatric Patients With COVID-19. (13th November 2020) - Pandey, Utsav; Yee, Rebecca; Shen, Lishuang; Judkins, Alexander R; Bootwalla, Moiz; Ryutov, Alex; Maglinte, Dennis T; Ostrow, Dejerianne; Precit, Mimi; Biegel, Jaclyn A; Bender, Jeffrey M; Gai, Xiaowu; et al.
Abstract: Background: The full spectrum of the disease phenotype and viral genotype of coronavirus disease 2019 (COVID-19) have yet to be thoroughly explored in children. Here, we analyze the relationships between viral genetic variants and clinical characteristics in children. Methods: Whole-genome sequencing was performed on respiratory specimens collected for all SARS-CoV-2-positive children (n = 141) between March 13 and June 16, 2020. Viral genetic variations across the SARS-CoV-2 genome were identified and investigated to evaluate genomic correlates of disease severity. Results: Higher viral load was detected in symptomatic patients ( P = .0007) and in children <5 years old ( P = .0004). Genomic analysis revealed a mean pairwise difference of 10.8 single nucleotide variants (SNVs), and the majority (55.4%) of SNVs led to an amino acid change in the viral proteins. The D614G mutation in the spike protein was present in 99.3% of the isolates. The calculated viral mutational rate of 22.2 substitutions/year contrasts the 13.5 substitutions/year observed in California isolates without the D614G mutation. Phylogenetic clade 20C was associated with severe cases of COVID-19 (odds ratio, 6.95; P = .0467). Epidemiological investigation revealed major representation of 3 of 5 major Nextstrain clades (20A, 20B, and 20C) consistent with multiple introductions of SARS-CoV-2 in Southern California. Conclusions: Genomic evaluation demonstrated greater than expected genetic diversity, presence of the D614G mutation, increased mutation rate, and evidence of multiple introductions of SARS-CoV-2 into Southern California. Our findings suggest a possible association of phylogenetic clade 20C with severe disease, but small sample size precludes a definitive conclusion. Our study warrants larger and multi-institutional genomic evaluation and has implications for infection control practices.